Assessment of Mental Disorder as a Predictor of Criminal Behaviours in Nigeria - Ruwan, Ibrahim Ignatius Felix; Fadare, Gbenga Oba; Garba, Musa Yusuf; Jose, Charlton; Ogechukwu, Odoh Priscilia (NIU Journal of Humanities, 2021)
The study examined mental disorder as a predictor of criminal behaviours among young adults. Sectional design was adopted and convenience sampling technique was used to draw the sample. A total of 141 participants were used. An average age of 21.50 years (SD = 2.19) was found. One hundred and seven (107) (75.9%) of all participants were male and thirty four (34) (24.1%) were female. Two instruments were used for data collection: NPD subscale of the Personality Diagnostic Questionnaire (PDQ-4+) and antisocial behavior questionnaire (ASBQ). It was hypothesized that narcissistic personality disorder will not significantly predict antisocial behavior among young adults. Regression results showed that Narcissistic Personality Disorder (NPD) (Î² = .570, t = 8.17, p< .001) is a significant predictor of Antisocial Behaviour (ASB) among young adults, therefore, the null hypothesis was rejected. In Conclusion , Mental illness is a very broad concept; however, various mental illnesses have been linked to criminal behavior. This implies that individuals with narcissistic personality disorders are predisposed to criminal behaviours. Based on the findings of the study, it was recommended were that the services of psychologists should be employed in the law courts to examine the mental health of offenders, to aid the jury in deciding if they should be sent to prison or a psychiatric hospital for rehabilitation. Keywords: Criminal behavior, Mental disorder, Narcissistic, Nigeria, Personality